The judicial practice of “impeccable lifestyle” (Academic Journal of Internal Affairs, 2016)
The author provides an overview of how the recently introduced requirement for ”impeccable lifestyle” for law enforcement officials has been implemented in practice in Hungary.
Keywords: impeccable lifestyle; law enforcement officials; practice